Strand 3: A hybrid network learning approach for technical education built around on-the-job training - Vescoukis, V.C.; Retalis, S. (Proceedings of the International Conference on Networked Learning, 1998)
Much has been said and written on the use of New Technologies in all levels of education and vocational training. There is no doubt that the emergence of technology will have a great impact on the look and feel of life in the future, including the way people acquire knowledge. All around the world, the educational systems strive to meet these new challenges. Many authors point out the fact that New Technology is used not only as a tool, but also as a target itself and raises important pedagogical issues. Although several experiments are already being conducted, much remains to be done in the design and evaluation of new learning environments in all fields and levels of education. We have been working in a real educational environment of secondary technical vocational education, exploiting the possibilities of strong learner participation in a learning context combining traditional classroom training, on-the-job training and Network-Based training. The main concept of our approach lies in the fact that practical on-the-job training is among the most valuable elements of secondary technical education. This activity can produce quire interesting results if effectively supported by a network learning environment (NLE). In our approach, the content of the learning material within this environment is enriched by training material produced by the trainees themselves during their on-the-job training activities. The design, partial implementation and some lessons learned during this effort are presented in this paper.